The Surreal and the Underground in Ali Teoman's The Triology of Konstantiniyye - Oezkan, Ahmet Ferhat (Rector Ciu Cyprus Int Univ, 2025)
The Trilogy of Konstantiniyye (1962-2011) comprises three novels titled Uykuda & Ccedil;ocuk & Ouml;l & uuml;mleri (Deaths of Children in Sleep, 2002), Karadelik G & uuml;ncesi (Black Hole Diary, 2007), and Gecenin Atlar & imath; (Horses of the Night, 2011). It features a complex structure characterized by intertextuality, innovative language, and profound imagination. Each volume of the trilogy features distinct main characters and evolving plots; nonetheless, all three novels possess two shared characteristics: Surrealist realm where dream and reality synthesize, and their settings situated underground. The two mutually reinforcing aspects of The Trilogy of Konstantiniyye, along with other fictional elements, create a pattern that aligns with the fundamental principles and artistic techniques of surrealism to emancipate consciousness. Consequently, examining the subterranean places in these books, whose classification and characterization are contentious, yields valuable insights into elucidating the surrealist attributes of these works. To achieve these conclusions, rather than providing a detailed analysis of the extensive spaces in the books, the underground spaces were analyzed in conjunction with the items they contained and their historical context. Surrealism seeks to attain the marvelous at the intersection of dream and reality. This notion, analogous to uncanny in psychoanalytic discourse, is most prominently manifested in romantic ruins and modern mannequins. The examination of the underground romantic ruins and surreal artifacts of the trilogy elucidates the convergence of the fiction with surrealist techniques. This study aims to clarify the path of fiction into the underground, the liberation of consciousness, and the surrealist domain created in The Trilogy of Konstantiniyye, by employing surrealist techniques and concepts, drawing on both literary texts and theoretical writings from surrealists who have made substantial contributions to the novel genre.
Keywords: Ali Teoman; The Trilogy of Konstantiniyye; surrealism; the space; the marvelous